2014
DOI: 10.1128/aac.03685-14
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Teicoplanin in Children

Abstract: Teicoplanin is frequently administered to treat Gram-positive infections in pediatric patients. However, not enough is known about the pharmacokinetics (PK) of teicoplanin in children to justify the optimal dosing regimen. The aim of this study was to determine the population PK of teicoplanin in children and evaluate the current dosage regimens. A PK hospital-based study was conducted. Current dosage recommendations were used for children up to 16 years of age. Thirty-nine children were recruited. Serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
6
30
0
1
Order By: Relevance
“…All these three studies in adults have shown that the population pharmacokinetics of teicoplanin were well described by a two compartment model and the elimination of teicoplainin was significantly influenced by renal function. Our findings are also in agreement with those of a pharmacokinetic study in critically ill children, showing that 54% of patients had C ss,min <10 mg l –1 with the current dose regimen . There are very limited data in neonates.…”
Section: Discussionsupporting
confidence: 91%
“…All these three studies in adults have shown that the population pharmacokinetics of teicoplanin were well described by a two compartment model and the elimination of teicoplainin was significantly influenced by renal function. Our findings are also in agreement with those of a pharmacokinetic study in critically ill children, showing that 54% of patients had C ss,min <10 mg l –1 with the current dose regimen . There are very limited data in neonates.…”
Section: Discussionsupporting
confidence: 91%
“…This comparison was based on Monte Carlo simulations conducted on a previous teicoplanin PK study with older children and adults. 6 Exposure -response relationships A newly described PD index (AUC:EC 50 ) was used to link drug exposure with therapeutic response (terminal CRP concentration). 21 An E max sigmoidal model was fitted to the data.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…4,5 In older children, there is considerable pharmacokinetic (PK) variability in comparison with adults, with a much wider drug exposure (AUC) distribution among children. 6 Little is known about the pharmacokinetics (PK) of teicoplanin in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The summary of the research available showed that patients are not achieving target concentrations. This retrospective audit aimed to evaluate whether patients were achieving target serum concentrations.…”
mentioning
confidence: 99%